Causes, Effects and Remedies of Examination Malpractice among Senior Secondary School Students in Osun State - Olamoyegun Stephania Olabisi; Aibe Joseph Ndayebom; Ahmed Foluke Margaret; Ogunode Niyi Jacob (Researchparks Publishing, 2022)
The study investigated the causes, effects and remedies of examination malpractice among senior secondary school students in Osun State. In other to achieve the objectives of the study, four research questions were raised. The population of the study consisted of ten thousand, eight hundred and thirty- four SSII students (10,834) of three hundred and twenty- one senior secondary schools in Osun State. The sample size of the study was 707 drawn across 32 senior secondary schools in Boripe, Ifelodun and Odo-Otin Federal Constituencies in Osun State. The instrument used was questionnaire on causes, effects and remedies of examination malpractice on senior secondary school students (CEREMSSSS). Data collected were analyzed using descriptive and inferential statistics. The reliability coefficient of the instrument was found to be 0.80. The findings of this study showed that there is no significant difference in the opinion of male and female students on causes, effects and remedies of examination malpractice. The students strongly agreed that inadequate instructional resources for effective teaching, inadequate qualified teachers, curriculum contents being too wide, inability of teachers to finish scheme of work and inability of teachers to combine examination syllabus with teaching syllabus are the major causes of examination malpractice. They also strongly agreed that when students are students are well taught and assessed, when examination supervision is properly done, when more qualified teachers are employed, and more infrastructure and teaching materials are provided, examination malpractice would be curbed. Based on the findings, the following recommendations were made: More qualified teachers should be employed, infrastructure and instructional materials should be adequate, supervision of examination should be properly done and corrupt examination officials, and school management, teachers and students should be thoroughly punished based on examination malpractice act. Government should also deemphasize possession of paper certificates and lay serious emphasis on skill acquisition, where parents should continue to encourage their children to study and not be the one taking them to miracle centers.